2017
DOI: 10.1038/s41598-017-06313-w
|View full text |Cite
|
Sign up to set email alerts
|

After infection with Leishmania infantum, Golden Hamsters (Mesocricetus auratus) become more attractive to female sand flies (Lutzomyia longipalpis)

Abstract: In Brazil, human and canine visceral leishmaniasis is caused by infection with Leishmania infantum, a Protist parasite transmitted by blood-feeding female Lutzomyia longipalpis sand flies. The objective of this study was to determine if the odour of hamsters, infected with Le. infantum, was more attractive than the odour of the same hamsters, before they were infected. The attractiveness of odour collected from individual hamsters (n = 13), before they were infected, was compared in a longitudinal study, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 32 publications
1
28
2
Order By: Relevance
“…have shown increased attractiveness to malaria vectors and differences in the volatile compounds released by these hosts [1518]. The same pattern has been suggested for the aetiological agent of visceral leishmaniasis, since increased attractiveness of Leishmania infantum- infected hosts to the parasite’s vector Lutzomyia longipalpis has been demonstrated [19,20]. In a cross-sectional study, when different uninfected and infected animals were evaluated in the same moment, it was suggested that differences in the attractiveness of L .…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…have shown increased attractiveness to malaria vectors and differences in the volatile compounds released by these hosts [1518]. The same pattern has been suggested for the aetiological agent of visceral leishmaniasis, since increased attractiveness of Leishmania infantum- infected hosts to the parasite’s vector Lutzomyia longipalpis has been demonstrated [19,20]. In a cross-sectional study, when different uninfected and infected animals were evaluated in the same moment, it was suggested that differences in the attractiveness of L .…”
Section: Introductionmentioning
confidence: 78%
“…infantum exhibited increased attractiveness to L . longipalpis [20]. Until now, among more than 30 species of Leishmania , no study on this topic has addressed species that cause cutaneous leishmaniasis.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, studies in Lu. longipalpis showed a preference for volatile compounds from hamsters infected with L. infantum in comparison with non‐infected hamsters (Nevatte et al ., ). This possible host modification by the parasite has been also demonstrated for Plasmodium sp.…”
Section: Percentages Of Lutzomyia Longipalpis Males and Females Activmentioning
confidence: 97%
“…longipalpis after infection. These results suggest a parasite‐induced modification of the host metabolism for the production of VOCs as a way of attracting vectors and increasing their dissemination (Nevatte et al ., ). The present study was not designed to discuss the possible modification of infected dogs by L. infantum to induce the emission of VOCs in these hosts.…”
Section: Percentages Of Lutzomyia Longipalpis Males and Females Activmentioning
confidence: 97%
“…The odours of golden hamsters infected with Le. infantum are more attractive to female sand flies than the odours of uninfected hamsters (O'Shea et al, 2002;Nevatte et al, 2017). The odour obtained from the hair of dogs infected with Le.…”
Section: Introductionmentioning
confidence: 99%